2020
DOI: 10.1016/j.eclinm.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up screening and treatment for elimination of hepatitis C among men who have sex with men in the era of HIV pre-exposure prophylaxis

Abstract: Background: Routine HIV pre-exposure prophylaxis (PrEP) and HIV care appointments provide opportunities for screening men who have sex with men (MSM) for hepatitis C virus infection (HCV). However, levels of screening required for achieving the WHO elimination target of reducing HCV incidence by 90% by 2030 among all MSM are unknown. Methods: An HCV/HIV transmission model was calibrated to UK prevalence of HIV among MSM (4¢7%) and chronic HCV infection among HIV-positive MSM (9¢9%) and HIV-negative MSM (1.2%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Specific behavioural and educational programmes are required, but such interventions may be difficult to implement because MSM using chem‐sex usually do not identify themselves as drug users [33]. Enrolment in HIV pre‐exposure prophylaxis (PrEP) programmes might reduce HCV incidence due to a reduction in risky behaviour [34], but they do not seem to achieve it, probably because HIV‐infected MSM and HIV‐negative MSM using PrEP share similar risk practices [35]. In fact, a recent study in a cohort of HIV‐negative MSM using PrEP in the Netherlands reported high IR of RAHC and of HCV reinfection, similar to the rates that we have found herein [36].…”
Section: Discussionmentioning
confidence: 99%
“…Specific behavioural and educational programmes are required, but such interventions may be difficult to implement because MSM using chem‐sex usually do not identify themselves as drug users [33]. Enrolment in HIV pre‐exposure prophylaxis (PrEP) programmes might reduce HCV incidence due to a reduction in risky behaviour [34], but they do not seem to achieve it, probably because HIV‐infected MSM and HIV‐negative MSM using PrEP share similar risk practices [35]. In fact, a recent study in a cohort of HIV‐negative MSM using PrEP in the Netherlands reported high IR of RAHC and of HCV reinfection, similar to the rates that we have found herein [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, significant HCV infection resides in HIV‐negative MSM (1.2% prevalence in UK in 2008/2009), 7 especially among those on HIV pre‐exposure prophylaxis (2.1% in PROUD study) 8 . Although three recent European studies have demonstrated scaling‐up HCV treatment can result in substantial reductions (51%–77%) in HCV incidence among HIV‐positive MSM, 6,9,10 our modelling suggests that screening and treatment is also needed in HIV‐negative MSM to reach the HCV elimination targets among all MSM 11 …”
Section: Introductionmentioning
confidence: 82%
“…We adapt a previous deterministic continuous‐time model of HIV and HCV transmission among all UK MSM 11,16 to include stages for HCV‐related liver disease progression and prior exposure to infection (full details and further parameter discussion in supplementary material Appendix ). The model (Figure ) stratifies MSM by compartments for HIV and PrEP status (susceptible on/off PrEP, acute HIV infection on/off PrEP, undiagnosed chronic HIV infection and diagnosed chronic HIV infection); HCV‐status (susceptible without HCV antibodies, susceptible with HCV antibodies, acute HCV‐infection, undiagnosed and diagnosed chronic HCV‐infection); stage of liver disease progression (undamaged, fibrosis stages F1 through to F4, decompensated cirrhosis, hepatocellular carcinoma (HCC), liver transplantation and post‐liver transplantation) and either low‐ or high‐risk sexual behaviour, defined by the number of anal sex partners (high‐risk defined as ≥15/year).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratifications by high and low injecting risk, with high-risk being defined as being homeless and/or a crack cocaine injector that has been shown to increase the risk of HCV infection acquisition among PWID, which results in more benefit of ‘treatment as prevention’. The future model could simulate the movement of MSM through different interaction behaviour with sexual partnerships [ 104 ], HIV pre-exposure prophylaxis states, and HIV infection status [ 105 ]. Stratifications by sexual partnerships could include ‘regular partnerships’ (relationships lasting more than one time step), ‘casual partnerships’ (individuals who meet up with for casual sex on more than one occasion), and ‘random partnerships’ (individuals who meet up with for only a single interaction) to capture different sexual risk and the potential compliance to treatment.…”
Section: Recommendations For Future Studiesmentioning
confidence: 99%